Pengaruh Penggunaan Kartu Konsep terhadap Kemampuan Bahasa Ekspresif pada Anak Berkebutuhan Khusus (ABK) di Klinik Hey Kids Kartasura - Fidya Istikqomah, Ariska; Soesyasmoro, R. Asto (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Children with Special Needs are children who have limitations in one or several abilities, both physical, such as blind, deaf, and psychological, such as autism and ADHD. The influence of the media in the form of picture cards on vocabulary, memory, and the subject's ability to mention vocabulary, so that the subject is not left behind in language skills. Objectives: This study aims to determine the effect of using concept cards on increasing expressive language skills in Children with Special Needs at the Hey Kids Kartasura Clinic. Methods: This study used a pre-experimental study with a one-group pretest-posttest design. The sampling technique used is total sampling with a total sample of 15 respondents. To find out whether there is an increase in expressive language skills, a pre-test and post-test were carried out on these respondents. The statistical test used in this research is the Paired T-Test. Results: The results of the study found that there was a significant effect between the use of concept cards on increasing expressive language skills in Children with Special Needs. The results of the Paired T-Test showed a P value (sig.) 0.010 (P <0.05 = Ha accepted). Conclusion: There is an effect of using concept cards on increasing expressive language skills in Children with Special Needs at the Hey Kids Kartasura Clinic. Keywords: Use of Concept Cards, Improving Expressive Language Skills, Children with Special Needs